Childhood Programs and Practices in the First Decade of Life : A Human Capital Integration - Reynolds, Arthur J.; Rolnick, Arthur J.; Englund, Michelle M.; Temple, Judy A. (Cambridge : Cambridge University Press, 2010)
Childhood Programs and Practices in the First Decade of Life presents research findings on the effects of early childhood programs and practices in the first decade of life and their implications for policy development and reform. Leading scholars in the multidisciplinary field of human development and in early childhood learning discuss the effects and cost-effectiveness of the most influential model, state, and federally funded programs, policies, and practices. These include Head Start, Early Head Start, the WIC nutrition program, Nurse Family Partnership, and Perry Preschool as well as school reform strategies. This volume provides a unique multidisciplinary approach to understanding and improving interventions, practices, and policies to optimally foster human capital over the life course.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).